Therapeutic Use of LSD in Psychiatry: A Systematic Review of Randomized-Controlled Clinical Trials - Fuentes, Juan José; Fonseca, Francina; Elices, Matilde; Farré, Magí; Torrens, Marta (Frontiers in Psychiatry, 2020)
Lysergic acid diethylamide (LSD) was studied from the 50s to the 70s to evaluate behavioural and personality changes, as well as remission of psychiatric symptoms in various disorders. LSD was used in the treatment of anxiety, depression, psychosomatic diseases and addiction. However, most of the studies were not performed under contemporary standards, and it has taken several decades for a resurgence of interest in LSD research and its therapeutic potential for psychiatry. The aim of this review is to identify controlled and randomized clinical trials that assess the potential use of LSD in psychiatry. PRISMA guidelines for systematic review were followed. A literature search of PubMed and MAPS databases was performed as well as a manual search of references from evaluated studies. Only randomized-controlled clinical trials were included. Study quality was systematically calculated by using the Cochrane Collaboration Tool for assessing risk of bias. A final selection of 11 articles was made after considering inclusion and exclusion criteria. LSD was administered to 567 patients in a dose ranging from 20 to 800 mcg. Despite the design heterogeneity of clinical trials, positive results were observed, thus revealing the therapeutic potential of LSD to reduce psychiatric symptomatology, mainly in alcoholism. The vast majority of authors describe significant and positive short-term changes in patients, despite the fact that in some studies an important homogenization was observed between the LSD treatment group and control group at long-term follow-up. Multiple variables regarding LSD treatment therapeutic approach and quality of experience were revealed and related to therapeutic outcomes. LSD is revealed as a potential therapeutic agent in psychiatry, mainly in the treatment of alcoholism. Despite the difficulty of designing proper double-blind clinical trials with this substance, new studies that conform to modern standards are necessary in order to strengthen our knowledge on its use and open new doors in the future.